Marcadores de doença aterosclerótica em pacientes infectados pelo HIV sem tratamento antirretroviral. - Silva, Érika Ferrari Rafael da [UNIFESP] (2010)
Introduction: After the introduction of antiretroviral therapy, aids has acquired an aspect of chronic disease and less deaths has occurred. The deaths related to aids are diminished but the proportion of deaths unrelated to aids,including cardiovascular disease are increasing, in part due to the side effects from the antiretroviral therapy. Objectives: To quantify the number of endothelial progenitor cells (EPC) and microparticles (MP) in HIV-infected naïve patients and compared with a control group. Besides the biochemical profile we evaluated subclinical atherosclerosis through carotid intimal medial thickening and endothelial function by flow mediated dilation. Methods: A case-control study, matched for age and gender, cross-sectional with blind analysis of the goals of biomarkers. Quantification of EPC and MP was done with flow cytometry, subclinical atherosclerosis and endothelial function by echo-Doppler with high resolution linear transducer. We included 68 subjects (35 HIV + and 33 controls) with a median age of 33 years, 80% were male and Caucasian. Results: The lipid profile differ between the groups for total cholesterol 156 mg / dL and 173 mg / dL (p = 0.02) and HDL-C 37 mg / dL and 47 mg / dL (p = 0.001) for case and control groups, respectively. The count of the CEP was lower in HIV-infected patients compared with control CD34 + / KDR + [0.02% vs. 0.09%, p = 0.045], but not to CD34 + / CD133 + and KDR + / CD133 +. The average number of platelet MP was similar between the groups 24 992 per mL of plasma in HIV-infected group and 26 642 mL plasma in control (p = 0.83). The counting of endothelial MP / mL of plasma differed between groups, being higher in HIV-infected group compared to control (1963 vs. 436, p = 0.003). The measurement of intimal medial thickening was similar between groups, but was found lower flow-mediated dilation [mean (SD)] in the HIV patients [9% (5%) versus 16% (10%), p = 0.03]. Conclusions: HIV + patients, before HAART had lower amounts of EPC and increased endothelial MP, along with endothelial dysfunction.